Delving into the relationship between teacher emotion regulation, self-efficacy, engagement, and anger: A focus on English as a foreign language teachers - Deng, Juan; Heydarnejad, Tahereh; Farhangi, Fariba; Farid Khafaga, Ayman (Frontiers in Psychology, 2022)
Due to the potent role of teachers’ emotion regulation in effective teaching, it seems essential to see how emotion regulation can contribute to other relevant teaching constructs. In this regard, the present study is intended to probe into the causal relationship among teacher emotion regulation, self-efficacy beliefs, engagement, and anger. In so doing, the Language Teacher Emotion Regulation Inventory (LTERI), The Teacher Sense of Efficacy Scale (TSES), The Engaged Teacher Scale (ETS), and The Teacher Anger Scale (TAS) were administered to 581 English as a Foreign Language (EFL) teachers in Iran. To gauge the causal relationships among the variables, confirmatory factor analysis (CFA) and structural equation modeling (SEM) using LISREL 8.80 were conducted. The results indicated that language teacher emotion regulation could positively and significantly predict teachers’ self-efficacy beliefs and engagement at work. Moreover, the influence of language teacher emotion regulation on the teacher’s anger is significantly negative. That is, the stronger emotion regulation is implemented the better teachers can manage their anger. The implications of this study may uncover new prospects for effective teaching, especially during the COVID-19 pandemic.